AC sine wave generation by using SPWM inverter - Islam, Md. Sakibul; Nuzhat, Farah; Nadim, Md. Nazmul Hoque (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.